PENGARUH KOLKISIN TERHADAP OPTIMALISASI MINYAK ATSIRI TANAMAN JAHE (Zingiber officinale Rosc.) - Reza Prakoso Dwi Julianto; Astri Sumiati; I Made Indra Agastya (Universitas Tribhuwana Tunggadewi, 2022)
The research aims to obtain the concentration and immersion time to increase the essential oil content, growth, and yield of ginger plants. This research used a split-plot design, with the main plots of ginger varieties and subplots of colchicine immersion time. Parameters observed included stem morphology, leaf morphology, root morphology, rhizome morphology, and essential oil content. The research results show that the optimal immersion time of colchicine with a four ppm dose to increase productivity in the three varieties of ginger was 12 hours. Immersion of 16 hours would reduce the productivity of ginger plants. Immersion using colchicine for 12 hours on white ginger and small white ginger varieties was able to increase the essential oil content to 1.79% and 2.31%, and also increasing essential oil would optimize for red ginger with immersion time for 16 hours was become 2.75%.